1999
DOI: 10.1086/314809
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Route of Immunization on Mucosal Immunity and Protection

Abstract: In macaques, the route of immunization has a profound effect on the immune response. Augmenting rectal or vaginal immunization with oral or nasal immunization enhanced the secretory IgA, serum IgG, and T cell responses. However, targeted iliac lymph node (TILN) immunization with recombinant simian immunodeficiency virus (SIV) gp120 and p27 elicited the most consistent mucosal antibody responses in the rectum, vagina, urine, seminal fluid, and blood. Both mucosal and TILN immunization induced specific CD4+ T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…It has been suggested that an HIV vaccine needs to elicit genital immune responses to effectively prevent heterosexual transmission (40,42,58,59). Thus, the first goal of the present study was to directly compare the effect of the route of immunization on i.vag.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that an HIV vaccine needs to elicit genital immune responses to effectively prevent heterosexual transmission (40,42,58,59). Thus, the first goal of the present study was to directly compare the effect of the route of immunization on i.vag.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a high frequency of virus-specific CD8 ϩ T cells in the cervicovaginal compartment, coupled with the notion that mucosal immunization may provide better protection against mucosal challenge than systemic immunization (3,4,30,31), has important implications for the development of vaccine modalities (57) that can target mucosal sites in order to prevent HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Virus variants that develop after infection are commonly characterized by sequence changes, length changes, and changes in the carbohydrate composition of the V1/V2, namely alterations in N-linked and O-linked glycosylation sites (1,7,53,55). In addition, the route of exposure to antigen in vaccine presentation, and potentially in infection, can affect the nature of the immune response (26,57).The analysis of env heterogeneity has yielded and will continue to yield important information about the biology of the viral Env protein. We have focused on the heterogeneity of the V1/V2 variable region to track changes in env gene populations, although other regions of env are amenable to similar analysis.…”
mentioning
confidence: 99%
“…Virus variants that develop after infection are commonly characterized by sequence changes, length changes, and changes in the carbohydrate composition of the V1/V2, namely alterations in N-linked and O-linked glycosylation sites (1,7,53,55). In addition, the route of exposure to antigen in vaccine presentation, and potentially in infection, can affect the nature of the immune response (26,57).…”
mentioning
confidence: 99%